Two offices for St-Elizabeth of Hungary - Haggh, Barbara (Ottawa The institute of mediaeval music, 1995)
"This is the first volume of Historiae, a series of editions of offices inaugurated by the Study Group 'Cantus Planus' of the International Musicological Society"--Pref., p. vii.Edited principally from a ms. in the Médiathèque municipale, Cambrai (Ms. 38).The musical and poetic evidence of the office Gaudeat Hungaria suggests that it represents the collaboration between Peter of Cambrai (fl. 1181-1236) and Gerard of St. Quentin (fl. 1248). The authorship of Letare Germania is unknown.--Cf. Introd